การลดจำนวนของพระสงฆ์และผลกระทบต่อพระพุทธศาสนาในอนาคต - บุญหนุน ชาญณรงค์ (Journal of Buddhist Studies Chulalongkorn University, 2019)
This article is adapted from the research project that aims to present the “Preliminary observation on the tendency of numbers and quality of Buddhist monks in rural Thailand,” funded by the Sirindhorn Anthropology Center in 2007. Its objectives are: (1) To study qualitative data concerning the conditions or causes of the decrease of Buddhist monks, and how it affects rural communities. (2) To present preliminary observations and suggestions that may serve as policy guidelines for dealing with the decrease in both number and quality of Buddhist monks in rural areas. It does so by studying documented statistical data of the numbers of Buddhist monks and novices between 1999-2006, as well as by conducting a field study in some areas of Chiangmai and Ubolratchatanee. The research finds that there has been a decrease in numbers of Buddhist monks and novices during the time of study. This decrease, however, is not related to economic factors of monks, but is due to the expansion of educational opportunities to rural areas. The Sangha does not have an educational system that is fitting for the changed social conditions and values. Changes in the rural labor sectors also contribute to the decrease, since rural families are having less offsprings, and prefer their sons to be ordained as monks only for short periods. Nevertheless, a survey of statistical data between 2007-2010 finds an increase in the number of monks and a decrease in that of novices, although the general number remains decreased.